ADDRESSING CHALLENGES IN THE SOUTH AFRICAN AFFORDABLE HOUSING MARKET: A CRITICAL REALIST PERSPECTIVE - Elizabeth Mirika MUSVOTO; Manya Mainza MOOYA (Journal of Construction Project Management and Innovation)
Since the advent of democracy, South African policymakers and researchers have been focusing on housing solutions. The South African affordable housing market has been battling with undesirable outcomes in terms of location, density, integration, and affordability. Housing is a complex multidimensional phenomenon that has been analysed from various perspectives. Various scholars have adopted either mainstream or institutional approaches in trying to explain housing outcomes, through examining the effects of regulations on housing provision. Oftentimes, such analysis has reached unfavourable conclusions on the actual causes of the outcomes in the housing market. The purpose of the article is to present a philosophical, theoretical and conceptual understanding of the study of affordable housing, which is critical in identifying variables for creating interventions to address challenges in the affordable housing market. This article employs a literature-based analysis of the theories and ontological approaches to housing development, key concepts of critical realism, and the relationship to structure-agency theory. Structure-agency theory is then applied to the South African affordable housing market. The challenges experienced by the South African affordable housing market are the same as those in both the developed and the developing world. The current view of the South African affordable housing market is not adequate to address the prevailing challenges. It is argued that a conceptual framework that is guided by a critical realist perspective and structure-agency theory will enable a better understanding of an interdisciplinary study such as that of housing. Such a framework provides insight into the structural dynamics that shape the roles, strategies, interests and decisions of various role players within a particular setting, leading to various outcomes. While this article draws on a critical realist perspective, it provides a platform to identify interventions in the affordable housing market that could influence policy formulation and implementation, and consequently, outcomes. The interventions identified will be limited to specific geographical locations, since there are various social and political factors at play; hence, the interventions cannot be generalised. The interventions identified in the affordable housing market through a critical realist perspective will inform policy implementation on how to provide integrated affordable housing in appropriate locations and at appropriate densities.